Torque and angulated retaining screw preload in implant supported prostheses - Schoeman, Johannes Hendrik (My University, 2020)
Purpose Angulated screw channel systems provide for screw-retained implant restorations in cases of leass than ideal implant positioning. Theoretical calculations predict a loss in abutment screw preload when the screw is torqued at an angle to the long axis of the implant. This in-vitro study aimed at measuring the loss in preload with a change in the angle of the applied torque and to determine to what value the torque should be increased to minimise the loss in preload for any specific angle.Method A custom built preload measurement device (Southern Implants, Irene, South Africa) was used to measure the preload achieved in the abutment screw (Dynamic Abutment® Solutions, Spain). A manual torque wrench applied torques ranging from 20 to 40 Ncm in 5 Ncm intervals at each angulation interval between 0° and 30° in 5° increments. Each test combination of angle and applied torque was repeated 4 times. Comparison of the preload between angles at a given torque were made by one-way ANOVA. Post-hoc comparisons were done using the Tukey-Kramer adjustment for multiple comparisons. The preload data were modelled using Ordinary Least Squares (OLS) regression. Results For all angles up to 20°, the preload had a positive linear relationship with all torques applied and was close to the value of the applied torque. At angles >20° a statistically significant loss in preload (p < 0.5) occurred for all torque values between 25 and 35 Ncm. At a torque of 20 Ncm, a significant loss in preload (p = 0.023) was seen at 30° whereas at 40 Ncm, a significant loss (p = 0.015) first occurred at 15°. Thus at higher angles a non-linear relationship appeared between preload and angle. The data allowed the use of a non-linear regression model to predict the change in preload as a function of both applied torque and angle. At the recommended torque value of 25 Ncm, a predicted 12.1% and 20.7% loss in preload occurred at angles 25° and 30° respectively. Conclusions In angulated screw channel systems, when the angular correction is >20° a significant loss in preload occurred when applying the recommended torque of 25 Ncm. To minimise the loss in preload a recommended increase in applied torque of 11% (torque to 28Ncm) for angles ranging between 20° and 25° and 24% (torque to 31Ncm) for angles greater than 25° should be applied.
A research report submitted in partial fulfilment of the requirement for the degree of Masters in Dentistry in Prosthodontics, School of Oral Rehabilitation to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020